1999
DOI: 10.1046/j.1365-2435.1999.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant species and nitrogen effects on soil biological properties of temperate upland grasslands

Abstract: Summary 1.The aim was to assess the extent to which the microbial biomass and activity, and community structure of fertilized upland grasslands are directly related to changes in soil N availability or indirectly related to individual plant species effects caused by changes in plant species composition and dominance. We investigated the short-term interactive effects of dominant plant species (Lolium perenne, Agrostis capillaris, Holcus lanatus and Festuca rubra) and nitrogen (N) amendment using an N-limited u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
213
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(238 citation statements)
references
References 48 publications
21
213
4
Order By: Relevance
“…The bacterial community structure (and nitrifier activity) can respond rapidly to changes in management, such as increased grazing and additions of animal urine (Le Roux et al 2008;Rooney & Clipson 2008;Singh et al 2009;Di et al 2010). The actinomycetes (a group of gram' bacteria) measured by PLFA were higher at HFC (P 00.01) and this is generally consistent with other studies showing that gram' bacteria often increase with increased intensity of grazing (Bardgett et al 1999;Klumpp et al 2009). Di et al (2009), however, suggested that AOA do not increase with N, but in our study there were significantly higher numbers of both AOA and AOB at HFC compared with LFC.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The bacterial community structure (and nitrifier activity) can respond rapidly to changes in management, such as increased grazing and additions of animal urine (Le Roux et al 2008;Rooney & Clipson 2008;Singh et al 2009;Di et al 2010). The actinomycetes (a group of gram' bacteria) measured by PLFA were higher at HFC (P 00.01) and this is generally consistent with other studies showing that gram' bacteria often increase with increased intensity of grazing (Bardgett et al 1999;Klumpp et al 2009). Di et al (2009), however, suggested that AOA do not increase with N, but in our study there were significantly higher numbers of both AOA and AOB at HFC compared with LFC.…”
Section: Discussionsupporting
confidence: 82%
“…This is higher than with other studies showing that fungi and fungal-feeding organisms are often reduced when soil N fertility and recycling increases (Coleman et al 1983;Bardgett et al 1999;De Vries et al 2006, 2007Lauber et al 2008;Krumins et al 2009). The mechanism is unknown but both are direct effects of fertilizer itself, and changes in the plant community and litter associated with fertilizers could be involved (Donnison et al 2000;Manning et al 2006).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Cattle have, for example, preferred resting and dunging areas, which may be different from their preferred grazing areas (Bokdam and Gleichman, 2000). In addition, the field studies compared existing situations with little control over the fields and independent variables (pseudoexperiment) (e.g., Bardgett et al, 2001;Donnison et al, 2000;Grayston et al, 2004) and microcosms were usually used in experiments (e.g., Bardgett et al, 1999;Jordan et al, 2003). Only a few studies used controlled field experiments (Clegg et al, 2003;Harrison and Bardgett, 2004;Wardle et al, 1999;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%